2019
DOI: 10.5604/01.3001.0013.3704
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of colorectal cancer contributes to its localization and advancement

Abstract: <b>Introduction:</b> Colorectal cancer is one of the most common cancers occurring in Poland. Unfortunately, this cancer is most often diagnosed at the time of great advancement. This is caused by the appearance of specific symptoms only in the late stages of cancer. Also, such low detection of early stages of adenocarcinoma may be caused by disregarding of slight symptoms. <br/>Purpose:</b> To analyse symptoms in patients with colorectal cancer and correlate with chosen clinical-pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The World Health Organization (WHO) estimates that the numbers of patients with CRC and CRC-related deaths will increase by 77 and 80% by 2030 [ 2 ]. The high mortality rate of CRC patients results from late diagnosis, which is due to the lack of clear physical symptoms at early stages [ 3 ]. Early resection, as permitted by early detection, is optimal CRC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that the numbers of patients with CRC and CRC-related deaths will increase by 77 and 80% by 2030 [ 2 ]. The high mortality rate of CRC patients results from late diagnosis, which is due to the lack of clear physical symptoms at early stages [ 3 ]. Early resection, as permitted by early detection, is optimal CRC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, including the cancer site, size, and stage, influence the symptoms of CRC [ 7 ]. Bleeding and altered bowel habits are the most frequent, with pain and bowel obstruction also common [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, including the cancer site, size, and stage, influence the symptoms of CRC [ 7 ]. Bleeding and altered bowel habits are the most frequent, with pain and bowel obstruction also common [ 7 - 10 ]. These symptoms can vary based on the location and stage of the cancer, with pain being more associated with colon cancer and fecal admixtures with rectal cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of breast cancer is increasing rapidly [1]. Of all cancers in women, breast cancer has the highest incidence rate and highest mortality rate [2]. Cancer remains a cause for concern despite the increase in physical and chemical therapies, and there are still many barriers to the treatment of breast cancer, such as adverse effects, arising from radiotherapy, surgery, and chemotherapy/hormonotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found in a screening test that the MeOH extract of L. cuneata exerted inhibitory effect on metabolic activity in MCF-7 human breast cancer cells, which led us to perform further phytochemical analysis and identify the bioactive compound(s) responsible for these effects. Bioassay-guided fractionation and chemical investigation of the MeOH extract led to the isolation of nine compounds (four lignan glycosides (1)(2)(3)(4), three flavonoid glycosides (5)(6)(7), and two phenolic compounds (8 and 9)). The structures of the isolated compounds were identified by LC-MS analysis and their spectroscopic data and physical data were compared with previously reported values.…”
Section: Introductionmentioning
confidence: 99%